Perspektif Masyarakat Tumbang Nusa terhadap Kegiatan Pemadam Kebakaran oleh Manggala Agni : The Community of Tumbang Nusa's Perspective on Fire Fighting Activities by Manggala Agni - Surasana, I Nyoman; Rizal, Moh; Kosmardianto, Hery (HUTAN TROPIKA, 2023)
The research aimed to assess villagers’s perception of Tumbang Nusa Village on the fire fighting activities (forest and land) by Manggala Agni (or Manggala Agni activities) and the relationship of each community's socio-economic variables with that view. The research is descriptive in nature using scoring, the object of research for the people of Tumbang Nusa Village, is analyzed by the Wilcoxon Rank Test and Chi Square Test. The results showed that there were differences in people's views on Manggala Agni activities between people who lived close to the fire disaster location and people who lived far from the fire location, there was also a relationship between the socio-economic variables of the community and the community's views on Manggala Agni activities.